2021
DOI: 10.21037/tlcr.2020.03.27
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive surgery in locally advanced N2 non-small cell lung cancer

Abstract: Locally advanced lung cancer, defined by nodal involvement in upper mediastinal stations (N2) (stage IIIA-N2), includes a wide spectrum of patients with multiple therapeutic alternatives. Such heterogeneity is explained, at least in part, by tumor size and magnitude of mediastinal nodal involvement.In this setting, many variants can influence the prognosis, such as the specific nodal stations compromised, the burden of mediastinal disease, and the presence of skip metastasis. In the surgical field, the advent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Although RATL has been widely accepted to be safe and effective for lobectomy and is being widely applied in treating early stage NSCLC, its application in advanced-stage NSCLC is still controversial [ 19 ]. Several retrospective studies have indicated RATL to be feasible and oncologically effective for the treatment of N2 NSCLC [ 8 , 14 , 20 ]. Recently, our team conducted a multicenter, randomized, controlled trial, which suggested that RATL improved perioperative outcomes and achieves similar long-term outcomes compared with open thoracotomy for clinical-N2 NSCLC patients [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RATL has been widely accepted to be safe and effective for lobectomy and is being widely applied in treating early stage NSCLC, its application in advanced-stage NSCLC is still controversial [ 19 ]. Several retrospective studies have indicated RATL to be feasible and oncologically effective for the treatment of N2 NSCLC [ 8 , 14 , 20 ]. Recently, our team conducted a multicenter, randomized, controlled trial, which suggested that RATL improved perioperative outcomes and achieves similar long-term outcomes compared with open thoracotomy for clinical-N2 NSCLC patients [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite open lobectomy (OL) still being the standard surgical procedure, video-assisted thoracoscopic lobectomy (VATL), a minimally invasive surgery (MIS) technique, has also been widely used for locally advanced NSCLC [ 6 ]. Multiple studies have indicated that VATL could reduce perioperative complications and short-term morbidities and also achieve comparable long-term outcomes to OL for NSCLC patients with positive N1 and/or N2 LNs, suggesting that MIS may be a favorable surgical approach for locally advanced NSCLC [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, lung cancer surgery can lead to severe postoperative pain [ 3 ]. With the popularization of video-assisted thoracoscopic minimally invasive surgery, the degree of postoperative pain has decreased compared with the degree of postoperative pain after open surgery, which is mainly due to the use of completely non-rib-spreading techniques [ 4 ]. Furthermore, with the widespread use of uniportal video-assisted thoracoscopic surgery (UVATS) techniques, postoperative pain is further relieved, which is mainly due to the minimal invasiveness of UVATS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The surgeon, by performing procedures with the robotic system, is able to achieve more accurate dissection, with consequent proper completeness of resection, precise pathological stage of the disease and favourable postoperative outcomes, as our experience has also confirmed. Furthermore, the minimally invasive approach may play a relevant role in the optimization of therapy, reducing postoperative recovery and allowing the appropriate timing of adjuvant therapy [27].…”
Section: Discussionmentioning
confidence: 99%